Business Opportunities in Maha Kumbh: A Study on Impact of Maha Kumbh Mela on Business Entrepreneur - Som, Gaurav; Gupta, Priya; Mishra, Moumita; Shivani, Shivani (Journal of Neonatal Surgery, 2025)
The Maha Kumbh Mela held every 144 years is one of the largest religious meetings globally, with more than 400 million visitors in 2025. The study examines the economic opportunities created for small business entrepreneurs during the event. Using secondary data, research analyzes business stability in areas such as income generation, employment generation and hospitality, transport and retail. Conclusions show that Maha Kumbh contributed more than 2 lakh crores to the economy, with 1.2 million jobs. Research underlines the importance of religious tourism in promoting local economies and provides insight into strategies to increase professional success in future events.